Project-Based Learning Interactive Multimedia with Orientation of Environmental Problems Assisted by Articulate Storyline 3 for Grade V Elementary Schools - Kadek Isya Andriyani Pratiwi; I Gede Margunayasa; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2023)
This research was motivated by the decline in learning outcomes in the learning content of IPAS and the use of media and learning models that could have been more optimal. This study aims to develop Interactive Multimedia based on the PjBL Model with an environmental problem orientation on Ecosystem material for grade V SD which is feasible, practical, and effective in improving student learning outcomes. This type of research is Research and Development (R & D) using the ADDIE model. The subjects of this study were four experts, three teachers, and six students, as well as 1 class V elementary school student totaling 25 people. This study used a pre-experimental design, one shot case study. The data collection methods were questionnaires and tests with instruments like rating scale sheets and multiple-choice tests. The data analysis technique used is descriptive quantitative and descriptive qualitative. The results showed that the feasibility score of media experts and learning content experts was 0.93 (very feasible), and the assessment of the practicality of the media by teachers was 98.52%. The practicality of the media by students was 99% (very good), and Interactive Multimedia based on the PjBL model effectively improved student learning outcomes in grade V Ecosystem material. This study concludes that the developed media is feasible, practical, and effective in improving the learning outcomes of fifth-grade students on Ecosystem material.